Utilization of Learning Video Media to Improve PAI Learning Outcomes in Elementary School IT Baitul Quran Panti - Hermi Yusnita (BiCED Proceeding, 2024)
This study aims to determine the effect of using video learning media on students' learning outcomes in Islamic Religious Education (PAI) at SD IT Baitul Quran Panti. This research uses a classroom action research (CAR) approach with two cycles. In Cycle I, it was found that students' learning outcomes were still not optimal, with some students not reaching the Minimum Mastery Criteria (KKM). However, after conducting reflection and improvements in Cycle II, students' learning outcomes showed significant improvement, with 81.2% of students achieving mastery. More structured learning activities and more effective use of video learning media in Cycle II contributed to the improvement in students' learning outcomes. This study will continue into Cycle III to achieve more optimal results.